2018
DOI: 10.1038/s41598-018-24587-6
|View full text |Cite
|
Sign up to set email alerts
|

Transient adhesion in a non-fully detached contact

Abstract: Continuous approaching and detaching displacement usually occurs in an adhesion test. Here, we found a transient adhesion force at the end of a non-fully detached contact. This force occurred when the nominal detaching displacement was less than the traditional quasi-static theory predicted zero force point. The transient adhesion force was ascribed to interfacial adhesion hysteresis, which was caused by the cracking process of the contact and the deformation competition between the sphere and supporting sprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
1
12
0
1
Order By: Relevance
“…Due to the importance of rough contacts for industry and daily life, there are many works done by different scientific groups with investigations of the particularities of contact between rough surfaces in the presence of adhesion. There are different experiments (Benz et al, 2006;Tiwari et al, 2017;Liu et al, 2018;Sahli et al, 2019), theories (Johnson, 1995;Persson, 2006;Persson and Scaraggi, 2014;Ciavarella, 2015;Papangelo et al, 2019), as well as computer simulations (Pastewka and Robbins, 2014;Rey et al, 2017;Li et al, 2019). A short historical review of the development of adhesion theories can be found in Popova and Popov (2018).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the importance of rough contacts for industry and daily life, there are many works done by different scientific groups with investigations of the particularities of contact between rough surfaces in the presence of adhesion. There are different experiments (Benz et al, 2006;Tiwari et al, 2017;Liu et al, 2018;Sahli et al, 2019), theories (Johnson, 1995;Persson, 2006;Persson and Scaraggi, 2014;Ciavarella, 2015;Papangelo et al, 2019), as well as computer simulations (Pastewka and Robbins, 2014;Rey et al, 2017;Li et al, 2019). A short historical review of the development of adhesion theories can be found in Popova and Popov (2018).…”
Section: Introductionmentioning
confidence: 99%
“…From figure it follows, that minimum F significantly increased for last three values of the velocity. This effect is due to viscoelasticity of rubber layer [8]. At big values of velocity, we observe bigger values of normal forces during detachment of indenter; for indenters with bigger radii this effect becomes more pronounced.…”
mentioning
confidence: 63%
“…Многочисленные эксперименты показывают, что в фазе индентирования γ eff принимает существенно меньшее значение, чем при отрыве. В результате это и приводит к наблюдаемому гистерезису [25,30,32,35]. Причина, приводящая к различным значениям эффективной поверхностной энергии, до сих пор не выяснена.…”
Section: формулировка модели и влияние времени покояunclassified